Strengthening Pancasila Values Through Scouting SMP Terpadu Al-Farabi - Abdul Fachruf; Syarbaini Saleh (MASI Mandiri Edukasi, 2025)
This study addresses the problem of declining internalization of Pancasila values among students, particularly in the context of character education. The objective is to explore how Scout extracurricular activities at SMP Terpadu Al-Farabi, Tanjung Anom, Deli Serdang, North Sumatra, serve as a medium to strengthen these values. The research specifically aims to examine how the principles of Pancasila—belief in God, humanity, unity, democracy, and social justice—are applied through Scouting activities and to identify the supporting and inhibiting factors affecting their implementation. A qualitative descriptive method was employed, using observation, interviews, and documentation as data collection techniques. The participants included the school principal, two Scout mentors, and ten eighth-grade students actively participating in the Scout program. The data were analyzed using the Miles and Huberman interactive model, involving data reduction, display, and conclusion drawing. The results indicate that Scout extracurricular activities significantly shape student character by embedding Pancasila values into daily practice. These are evident in students' discipline, teamwork, leadership, patriotism, and responsibility. However, the implementation faces obstacles, including limited facilities and inconsistent mentoring. Despite these challenges, the study finds that scouting remains a highly effective platform for civic education when properly supported and aligned with character-building goals.